Budgetary impact of state enterprises and what to do about it - Farrell, Trevor M. A. ([s.n.] Port of SpainTT, 1987)
Examines problem of public enterprises showing chronic losses which necessitate a continuous infusion of public funds. Outlines reasons why state enterprises are often financial failures. Discusses ways of solving the problem and makes recommendations for reducing the negative budgetary impact of state enterprises.